Viralitas Lato-Lato dalam Inovasi Pembelajaran di Pondok Pesantren Nurul Ichsan Bontang - Rosadi, Khumaini; Wahyuni, Rika (NABAWI: Jurnal Penelitian Pendidikan Islam, 2023)
The current viral game phenomenon, lato-lato. Consisting of two hard solid plastic balls a number of cold meatballs or ping pong balls with a small thin rope.  You  swing  your  finger  up  and  down  and  the  pendulum  has  to  be balanced to produce a rattling sound. Knock tok tok tok tok.The rhythm is also good, many students at the Nurul Ichsan Bontang Islamic Boarding School play it too, so there's nothing wrong with combining it with hadroh  blows  for  prayer.  In  addition  to  variations  in  the  treasures  of maulidan prayers. Increasingly adding to learning innovations at the Nurul Ichsan Islamic Boarding School.So  not  all  children's  play  is  negative.  Sometimes  it  is  positive  and  can become a new branch of e-sport, even a new knowledge.